Durability and microstructure of waste slurry based geopolymer concrete - Yifan Mao; Peng Zhang; Zhen Gao; Yuanxun Zheng; Mengyuan Zheng (Journal of Materials Research and Technology)
The utilization of waste slurry (WS), with poor mechanical properties, as a construction material offers a means for the problem of WS treatment. In this study, the WS with fly ash and slag powder (SP) were employed as the precursors to fabricate the waste slurry based geopolymer concrete (WSGPC). The influence of SP dosage, alkali activator (AA) dosage and AA modulus on the frost resistance, anti-permeability and shrinkage properties of WSGPC was investigated by the Taguchi orthogonal method. The results indicated that the frost resistance and anti-permeability of WSGPC exhibited a trend of initial increase and subsequent decrease as the AA dosage and AA modulus raise. Moreover, the aforementioned properties were significantly enhanced with the SP dosage rising, but it leads to a rising autogenous shrinkage and drying shrinkage. In light of the results of orthogonal experiments, the optimal mixture for WSGPC was ascertained as follows: the SP content of 60%, the AA dosage of 29% and the AA modulus of 1.3. The microscopic experimental outcome exhibited that the amorphous gels, filling the pores in WSGPC, were mounted up with the SP percentage raising. Additionally, the porosity of WSGPC declined gradually with the increment of SP dosage, while the pore size distribution of WSGPC was optimized. The findings suggested that employing WS to manufacture geopolymer concrete was viable, which can diminish the environmental pollution and realize the resource utilization.